PENGATURAN HAK CIPTA PERLINDUNGAN HUKUM KARYA SENI TRANSFORMASI - Made Aditya Pramana Putra (Universitas Tabanan, 2025)
Problems related to intellectual property rights, especially in the field of copyright, are very diverse. One of them is the phenomenon of modification of a copyright work that often occurs today in society. Based on that, the problems in this journal are (1) Does the author's right end after modification of the copyrighted work? (2) What is the form of control over the transformation work in Indonesia? The purpose of this paper is to explain the normative limitations given to copyrighted works protected by law after legal obscurity that allows the weakening of the intellectual property rights of the first creator; and can juridically answer the form of legal control given to a work modified by copyright protected work. The method used in this research is a type of normative legal research that is supported by a statutory approach, a case approach and a conceptual and analytical approach. The end result of this journal is that the modification of the transformative work does not abolish the author's right to gain economic benefits from his creation by taking into account a reasonable royalty fee between the creator and the related parties; as well as the forms of control exercised over transformative works in Indonesia, namely administratively and criminally